2005
DOI: 10.1007/s10384-004-0175-7
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative Lag Under Habitual Seeing Conditions: Comparison Between Myopic and Emmetropic Children

Abstract: Under binocular viewing conditions, myopic children when viewing the target through fully correcting glasses tend to show larger lags of accommodation than emmetropic children, but the lags of accommodation are usually reduced by their spectacle undercorrection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 19 publications
6
63
2
Order By: Relevance
“…Based on the amount of undercorrected myopia (UCM), children with undercorrection of myopia were further divided into four groups (0 D<UCM≤ 0.5D, 0.5D < UCM ≤ 1.0D, 1.0D < UCM ≤ 1.5D and UCM >1.5D). Accommodative lag was calculated using previous equations [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the amount of undercorrected myopia (UCM), children with undercorrection of myopia were further divided into four groups (0 D<UCM≤ 0.5D, 0.5D < UCM ≤ 1.0D, 1.0D < UCM ≤ 1.5D and UCM >1.5D). Accommodative lag was calculated using previous equations [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…30 and up to 1.5 D. 31 Our mean value at this distance with the SVL of 0.6 D is on the low side of the range but matches Tarrant,28 which is the only study among those listed above that was measuring young adults.…”
Section: Baseline La Using Single Vision Spectacle Lensesmentioning
confidence: 99%
“…In children, it was discovered that the mean lag of accommodation was higher in those with corrected myopia compared to those with emmetropia (Nakatsuka et al, 2005) Similarly, a higher lag of accommodation was found in young subjects who had developed myopia, i.e. it occurred after rather than before myopia onset (Mutti et al, 2006).…”
Section: Ciliary Muscle Accommodation (Tonic Accommodation and Accommentioning
confidence: 88%